How Do Disaster Relief Nurses in Japan Perceive and Respond to Risks? A Cross-Sectional Study - Aki Nishikawa; Takumi Yamaguchi; Yumiko Yamada; Hideko Urata; Tetsuko Shinkawa; Yuko Matsunari (MDPI AG, 2023)
This study assessed the risk perceptions among disaster relief nurses (DRNs) in Japan by focusing on 15 risk factors associated with frequent natural disasters and the ongoing coronavirus disease 2019 (COVID-19) pandemic. We conducted a cross-sectional study that targeted DRNs across six prefectures in Japan and explored nurses' perceptions of risks including radiation exposure, volcanic eruptions, and mass infections. The findings indicated a heightened perception of radiation and nuclear-related risks. In the context of the COVID-19 pandemic, DRNs perceived "mass infection" as a significant risk. An age-based analysis revealed that younger nurses had more dread about "mass infection" and had heightened uncertainty about the "X-ray test" compared with their older peers. Understanding DRNs' risk perceptions is crucial for effective disaster response preparedness and training. The study highlights the need to address these perceptions to ensure that DRNs are well prepared and supported in their roles. This study was not pre-registered on a publicly accessible registry.